2007
DOI: 10.1590/s1806-37132007000600005
|View full text |Cite
|
Sign up to set email alerts
|

A percepção do controle dos sintomas em pacientes asmáticos

Abstract: The incidence of poor perception of asthma control in asthma patients is high, especially in elderly patients with lower income and a lower degree of asthma severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…In this context, two Brazilian cities implemented distinct public health care programs for asthma (with the creation of referral centers, easy provision of medications, strict public health care protocols, and professional training) and were successful in achieving an important decrease in the number of asthma-related hospitalizations. 27 , 28 Moreover, in one of these cities (Salvador, in the state of Bahia), the implemented asthma control program showed that, when patients with severe asthma had their disease under control, there was a major decrease in the direct costs of asthma in the families (−89%) and an increase in the overall family income. 29 These local initiatives demonstrate the importance of implementing further effective asthma control programs in public health care systems.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, two Brazilian cities implemented distinct public health care programs for asthma (with the creation of referral centers, easy provision of medications, strict public health care protocols, and professional training) and were successful in achieving an important decrease in the number of asthma-related hospitalizations. 27 , 28 Moreover, in one of these cities (Salvador, in the state of Bahia), the implemented asthma control program showed that, when patients with severe asthma had their disease under control, there was a major decrease in the direct costs of asthma in the families (−89%) and an increase in the overall family income. 29 These local initiatives demonstrate the importance of implementing further effective asthma control programs in public health care systems.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by other authors corroborate the present results. 14 – 16 In the activity limitation subscale, older age was also a determinant of lower QoL scores. Most likely, the clinical presentation of asthma is also affected by aging processes in the respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…What could explain such a dissociation between perception and real control level in patients in Latin America (9,10) and in the patients described in the study by Ponte et al? (8) The answer is probably related to the change of the concept of control. The present guidelines (1,11) adopt a more rigid definition that consists of several parameters, in addition to symptom control, which makes this outcome (control) more difficult to achieve than is the simple suppression of the symptoms.…”
Section: Ufsc Federal University Of Santa Catarina Health Sciences Cmentioning
confidence: 99%
“…This partial or inadequate correlation between symptoms and expiratory flows has also been observed when we compare symptoms with the inflammatory process of the airways. (7) In this issue of the Brazilian Journal of Pulmonology, Ponte et al (8) report the experience of perception of symptoms in a less affluent population in Salvador. In a cross-sectional study, 289 patients with asthma, consecutively included with disease of varying severity, were evaluated using structured questionnaires, medication and functional evaluation, in order to determine their perception of the degree to which their symptoms were controlled.…”
mentioning
confidence: 99%